Faktor- Faktor yang Mempengaruhi Masyarakat Membeli Daging Ayam Boiler di Kabupaten Bangli - I GUSTI NGURAH YURI PUTRA; I MADE SUDARMA; A.A.A WULANDIRA SDJ (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
ABSTRACT The Factors Affecting People Buy Chicken Meat Boiler in Bangli Regency Chicken meat is one of the many meat that consumed by the consumer, because it relatively easy to be accepted, either from the taste, price easily get it and there is no obstacle from the social and religion. Chicken meat in a relatively short time become strategic commodity business and replace other farms in provide of meat. Consumption of product of livestock products in Indonesia continues to increase from year to year. This study aims to find out: (1) sources of supply of chicken meat sold in the market of Kidul and Kayuamba market and (2) the factors that determine the consumer's decision to purchase chicken meat. The results showed: (1) The source of supply of chicken meat in the Market of Kidul and Kayuamba come from the Bangli regency itself and (2) There are six factors that influence of the respondent’s decision to purchase chicken meat in Bangli Regency. The results showed that: (1) Source of chicken supply at Kidul market and Kayuamba market come from Bangli Regency that are subdistrict of Susut, Bangli, Tembuku and Kintamani and (2) the respondent's household income in individual have significant effect on the purchase of chicken meat. Keywords: Demand, People, Chicken Meat Boiler